Stasis-Maintenance-(Un)productive-Presence: Parenting a Disabled Child as Crip Time - Adam W. Davidson (Disability Studies Quarterly, 2020)
In what follows, I represent and analyze time as "crip time" in the context of parenting a child with disabilities. That is, I seek to challenge, reimagine, and even upend, the normalized structures that often order our lives in time and our expectations of what makes for a meaningful life in the present, and as a result, a desirable, or even possible future. Using Alison Kafer's Feminist, Queer, Crip as a foundation, in four autoethnographic accounts, recounting a typical day in my life with my 15-year-old son, I consider time as Stasis, Maintenance, (Un)productive, and Presence.
Keywords: autoethnography; parenting; crip time; children with disabilities